Insight into the dispersive mechanism of Carboxylated Nanofibrilllated cellulose for individual montmorillonite in water. (15th November 2019) - Sun, Chuan; Fang, Zhiqiang; Qin, Famei; Chen, Kaihuang; Wang, Jingyu; Ding, Zixian; Qiu, Xueqing
Abstract: Carboxylated nanofibrillated cellulose (CNFC) has emerged as a promising green dispersant to prepare stable aqueous individual montmorillonite (MMT) suspensions. Nevertheless, its underlying dispersive mechanism remains elusive. Herein, we attempt to unveil the dispersive mechanism of CNFC for individual MMTs in water by characterizing the interfacial interactions between the two components using a quartz crystal microbalance with dissipation monitoring (QCM-D) and an atomic force microscopy (AFM). Both electrostatic repulsion and steric hindrance contribute to the excellent stability of homogeneous individual MMT suspensions, and their individual contributions are dependent upon the dosage of CNFC dispersant. The electrostatic repulsive forces dominate over the van der Waals forces that trigger the aggregation of aqueous individual MMTs when the dosage of CNFCs is 2 wt% (based on individual MMTs). With increasing dosage of CNFC dispersant, the electrostatic repulsive forces between individual MMTs tend to be level off while the steric hindrance gradually becomes a dominant factor that influences the dispersion stability of aqueous individual MMT suspensions. Finally, the effect of the CNFC dispersant's dosage on the optical and mechanical properties of nanocomposite film made with CNFCs and CNFC-dispersed individual MMTs is investigated. Understanding the dispersing principle of CNFCs for individual MMTs in water could pave the way to extend the applications of MMT in numerous value-added fields such as high-performance nanocomposites and flexible electronics. Graphical abstract: Illuminate the disperse mechanism of Carboxylated Nanofibrillated as a green dispersant dispersing individual Montmorillonite at different dosage by AFM.Image 1